Provenance and paleogeography of post-Middle Ordovician, pre-Devonian sedimentary basins on the Gander composite terrane, eastern and east-central Maine: implications for Silurian tectonics in the northern Appalachians - Ludman, Allan; Hopeck, John; Berry, Henry (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2017)
ABSTRACT Recent mapping in eastern and east-central Maine addresses long-standing regional correlation issues and permits reconstruction of post-Middle Ordovician, pre-Devonian paleogeography of sedimentary basins on the Ganderian composite terrane. Two major Late Ordovician-Silurian depocenters are recognized in eastern Maine and western New Brunswick separated by an emergent Miramichi terrane: the Fredericton trough to the southeast and a single basin comprising the Central Maine and Aroostook-Matapedia sequences to the northwest. This Central Maine/Aroos-took-Matapedia (CMAM) basin received sediment from both the Miramichi highland to the east and highlands and islands to the west, including the pre-Late Ordovician Boundary Mountains, Munsungun-Pennington, and Weeks-boro-Lunksoos terranes. Lithofacies in the Fredericton trough are truncated and telescoped by faulting along its flanks but suggest a similar basin that received sediment from highlands to the west (Miramichi) and east (St. Croix). Deposition ended in the Fredericton trough following burial and deformation in the Late Silurian, but continued in the CMAM basin until Early Devonian Acadian folding. A westward-migrating Acadian orogenic wedge provided a single eastern source of sediment for the composite CMAM basin after the Salinic/Early Acadian event, replacing the earlier, more local sources. The CMAM, Fredericton, and Connecticut Valley-Gaspé depocenters were active immediately following the Taconian orogeny and probably formed during extension related to post-Taconian plate adjustments. These basins thus predate Acadian foreland sedimentation. Structural analysis and seismic reflection profiles indicate a greater degree of post-depositional crustal shortening than previously interpreted. Late Acadian and post-Acadian strike-slip faulting on the Norumbega and Central Maine Boundary fault systems distorted basin geometries but did not disturb paleogeographic components drastically.